Productive Capital and Technical Efficiency in the UE-15 - Maria Jesus Delgado; Inmaculada Alvarez (European Regional Science Association (ERSA), 2003)
In this research we examine the capitalization process in the UE-15 with the aim to establish if the evolution manteined in the last two decades for the public capital and its distribution related private capital have conditioned the technical efficiency of the European economies. In this analysis we use the frontier function approach that allows to consider an inefficiency use of the productive factors. Specifically, we employ the parametric stochastic frontier model from Battese and Coelli (1995) to explore the determinants of the technical efficiency. The results show that larger endowments of public capital may facilitate the access of the productive activity to the levels of the more efficient members. We also find a limit to the capacity of introducing improvements in the use of productive factors, and it is related to private capital, then if the increase of public capital does not lead to an optimal distribution of this factor, the effect on efficiency will be negative.
Keywords: 330